2011
DOI: 10.1080/07060661.2011.600335
|View full text |Cite
|
Sign up to set email alerts
|

A TaqMan real-time PCR assay targeting the cytochrome o ubiquinol oxidase subunit II gene for detection of several pathovars ofPseudomonas syringae

Abstract: The identification and detection of eight pathovars of Pseudomonas syringae, bacterial pathogens of several important agricultural plants, was achieved by TaqMan real-time polymerase chain reaction of a specific DNA fragment of the cytochrome o ubiquinol oxidase gene. Under optimal real-time PCR conditions, the selected primers and probe were specific for the detection of pathovars syringae, tomato, maculicola, tabaci, atropurpurea, phaseolicola, pisi and glycinea. Two pathovars (coriandricola and morsprunorum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Schaad et al 1995 reported an assay sensitivity of 3-15 cells per reaction using a nested PCR. The sensitivity of the hydrolysis probe qPCR used here was stated to be 4.5 × 10 3 CFU ml − 1 , or approximately 4 cells per reaction if using 1 µl of bacterial suspension as template (Xu and Tambong 2011). There is a one-to-one relationship between amplification and bacterial number as there is only a single copy for the cytochrome o ubiquinol oxidase subunit II gene for P. savastanoi pv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schaad et al 1995 reported an assay sensitivity of 3-15 cells per reaction using a nested PCR. The sensitivity of the hydrolysis probe qPCR used here was stated to be 4.5 × 10 3 CFU ml − 1 , or approximately 4 cells per reaction if using 1 µl of bacterial suspension as template (Xu and Tambong 2011). There is a one-to-one relationship between amplification and bacterial number as there is only a single copy for the cytochrome o ubiquinol oxidase subunit II gene for P. savastanoi pv.…”
Section: Discussionmentioning
confidence: 99%
“…With a 6 Mbp genome with 58% G + C (Noble et al 2020), 100 fg DNA represents 15.5 copies of the genome, which suggests a lower sensitivity for qPCR on extracted DNA versus direct bacterial suspensions used as template. However, as Xu and Tambong (2011) failed to state the template volumes or develop a risk assessment of a seed lot's potential for disease outbreak and severity. Once implemented, molecular diagnosis could be further leveraged to include other diseases such as tan spot in a dual diagnostic qPCR to transform the way clean seed is delivered to growers, leading to cleaner planting seed, higher yields and economic gains for growers and the industry.…”
Section: Discussionmentioning
confidence: 99%
“…The locus tag for this fragment is CMN_00274. Primers were designed and tested for specificity, as reported previously [ 5 , 32 ]. The primers were checked for melting temperature (Tm), dimer or hairpin formation using an oligonucleotide properties calculator [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Seed crops should be grown in climates and locations non-conducive to pathogens, under drip irrigation to limit the amount of free moisture, and far removed from commercial crops (Grogan and Kimble 1967;Webster et al 1983;Gitaitis and Walcott 2007). Confirming the presence of pathogens in planting seed by using diagnostic assays such as serology, culturing and PCR further reduces the risk of epidemics (Vuurde et al 1991;Prosen et al 1993;Marques et al 2000;Rico et al 2006;Xu and Tambong 2011). Ultimately, managing the transmission of seed-borne diseases relies on precise identification of the target pathogens in planting seed and the development of targeted resistance to the pathogens within the host species (Bastas and Sahin 2017).…”
Section: Management Strategiesmentioning
confidence: 99%